Searches for the Higgs boson decaying to W^{+} W^{-} -> l^{+}nu l^{-}nubar with the CDF II detector - Collaboration, CDF; Aaltonen, T; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Arisawa, T; Artikov, A; Asaadi, J; et al. (2013)
We present a search for a standard model Higgs boson decaying to two $W$ bosons that decay to leptons using the full data set collected with the CDF II detector in $\sqrt{s}=1.96$ TeV $p\bar{p}$ collisions at the Fermilab Tevatron, corresponding to an integrated luminosity of 9.7 fb${}^{-1}$. We obtain no evidence for production of a standard model Higgs boson with mass between 110 and 200 GeV/$c^2$, and place upper limits on the production cross section within this range. We exclude standard model Higgs boson production at the 95% confidence level in the mass range between 149 and 172 GeV/$c^2$, while expecting to exclude, in the absence of signal, the range between 155 and 175 GeV/$c^2$. We also interpret the search in terms of standard model Higgs boson production in the presence of a fourth generation of fermions and within the context of a fermiophobic Higgs boson model. For the specific case of a standard model-like Higgs boson in the presence of fourth-generation fermions, we exclude at the 95% confidence level Higgs boson production in the mass range between 124 and 200 GeV/$c^2$, while expecting to exclude, in the absence of signal, the range between 124 and 221 GeV/$c^2$.